The Family Support in Career Decision Making in Students - Cholili, Abd Hamid; Arribath, Adrew Fahlevi; Fajria, Nadya Devianti Zahratul; Basith, Abdul (Proceedings Conference Psychology and Flourishing Humanity; Vol 2 No 1 (2025): Proceedings Conference on Psychology and Flourishing Humanity, 2026)
This study aims to determine the effect of family support on career decision-making in college students. The study used a quantitative approach with a correlational design. The number of participants was 35 people selected by purposive sampling. The instruments used included the Family Support Scale (12 items) and the Career Decision-Making Scale (12 items). Data analysis was carried out using SPSS 26 through reliability, normality, linearity, and simple regression tests. The results showed that family support had a significant effect on career decision-making (p = 0.007, R² = 0.257), meaning that family support had a 25.7% influence on college students' career decision-making. This article was developed by integrating the results of recent research (2019–2025), which showed that family support, career adaptability, and career self-efficacy were closely related to the clarity of college students' career goals.